Tuberculous otomastoiditis: A diagnostic dilemma - Yee, Pui Mun; Othman, Iylia Ajmal (2024)
Where tuberculous (TB) infection is prevalent, the diagnosis of TB otomastoiditis (TOM) should be considered in a chronically discharging ear that does not respond to standard medical treatment. We are reporting a case of TB otomastoiditis with an adjacent deep neck abscess in a healthy 18-year-old male. He presented with a five five-month history of right otorrhea with hearing loss and a concurrent right level two neck swelling, without any signs of acute infection. Aural polyp was seen occupying the external ear canal (EAC) obscuring the tympanic membrane. There was no clinical improvement despite oral, topical, and intravenous antimicrobial therapy. The audiogram showed right moderate to severe mixed hearing loss. Erythrocyte sedimentation rate (ESR) and Mantoux were positive; however, initial pus swab culture yielded Pseudomonas aeruginosa and was negative for acid-fast Bacilli (AFB). High-resolution computed tomography (HRCT) of the temporal bone showed multifocal bony erosion with soft tissue density occupying the EAC, middle ear, and mastoid air cells. Bezold and Citelli abscesses were also noted adjacent to the mastoid tip with an eroded outer cortex. The patient underwent mastoid exploration to obtain tissue for diagnosis and to clear the disease. The diagnosis of TB otomastoiditis was made based on intraoperative findings of caseous necrosis, which was culture positive for Mycobacterium tuberculosis but negative on AFB stain. Complete resolution of the disease was seen after three months of anti-TB treatment. His right hearing remains poor, thus he was counseled for a bone conduction hearing amplification device. High clinical suspicion and early HRCT will expedite the delivery of treatment for suspected TB otomastoiditis. In some cases, surgical intervention is needed to obtain tissue for diagnosis, remove the sequestrum, and when there is clinical evidence of complications.